1991
DOI: 10.1016/0014-5793(91)80141-o
|View full text |Cite
|
Sign up to set email alerts
|

A conformational switch involving the 915 region of Escherichia coli 16 S ribosomal RNA

Abstract: A novel alternative conformation, which involves an interaction between the 5′ terminal and 915 regions (E. coli numbering), is proposed after a screening of compiled sequences of small subunit ribosomal RNAs. This conformation contains a pseudoknot helix between residues 12–16 and 911–915, and its formation requires the partial melting of the 5′ terminal helix and the disruption of the 17–19/916–918 pseudoknot helix of the classical 16 S rRNA secondary structure. The alternate pseudoknot helix is proximal to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
1
9
2
Order By: Relevance
“…These results have recently been confirmed by Meier et al, (1994). Pinard et al, (1993) investigated the idea that the 5' proximal helix of the ribosome is involved in streptomycin binding by a conformational change to stabilize the binding of the drug (Leclerc & Gingras, 1991 ). Four mutations (13 u-A, 13U-c, 914 A-U and 914 A-G) were introduced, either individually or as double mutations ( 13 u-A and 914 A-U or 13U-C and 914 A-+G) into E. coli.…”
Section: Ribosomal Rna Mutationssupporting
confidence: 63%
“…These results have recently been confirmed by Meier et al, (1994). Pinard et al, (1993) investigated the idea that the 5' proximal helix of the ribosome is involved in streptomycin binding by a conformational change to stabilize the binding of the drug (Leclerc & Gingras, 1991 ). Four mutations (13 u-A, 13U-c, 914 A-U and 914 A-G) were introduced, either individually or as double mutations ( 13 u-A and 914 A-U or 13U-C and 914 A-+G) into E. coli.…”
Section: Ribosomal Rna Mutationssupporting
confidence: 63%
“…With regard to helices 2 and 27, we have already noted above that the potential base-pairs (Lodmell et al, 1995) between nucleotides 885 to 887 and 910 to 912 (the latter being part of the connecting strand between the two helices; Figure 1), can be formed only if the pseudoknot helix 2 becomes unpaired; a number of dynamic models have been proposed (e.g. see Leclerc & Brakier-Gingras, 1991) suggesting just such a process.…”
Section: Discussionmentioning
confidence: 95%
“…streptomycin and neomycin-like aminoglycosides, have also been suggested to bind to specific helices in 16S rRNA. For example, streptomycin may interact with nucleotides in the helix formed by the regions 12-16 and 911-915 (18). Footprinting experiments had already shown that streptomycin protects the residues 911-915 (8).…”
Section: Discussionmentioning
confidence: 99%